2020
DOI: 10.1021/acs.nanolett.0c03800
|View full text |Cite
|
Sign up to set email alerts
|

The Physics of Interlayer Exciton Delocalization in Ruddlesden–Popper Lead Halide Perovskites

Abstract: Two-dimensional (2D) lead halide Ruddlesden–Popper perovskites (RPP) have recently emerged as a prospective material system for optoelectronic applications. Their self-assembled multi quantum-well structure gives rise to the novel interwell energy funnelling phenomenon, which is of broad interests for photovoltaics, light-emission applications, and emerging technologies (e.g., spintronics). Herein, we develop a realistic finite quantum-well superlattice model that corroborates the hypothesis of exciton delocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Recently, our group also demonstrated a possibility of an ultrafast coherent localization of excitation in high-n QWs. [21] Such energetic disorder is proposed as a possible cause of the differences in the reported dynamics of the energy cascade. [16] In the context of average excess energy loss of carriers, the coherent process will facilitate sub-ps localization of carriers into high-n QWs (out-competing extraction, that we estimated previously to be of the order of tens of ps) where BCP can no longer extract them.…”
Section: Probing the Effect Of Organic Spacer With Two-dimensional El...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group also demonstrated a possibility of an ultrafast coherent localization of excitation in high-n QWs. [21] Such energetic disorder is proposed as a possible cause of the differences in the reported dynamics of the energy cascade. [16] In the context of average excess energy loss of carriers, the coherent process will facilitate sub-ps localization of carriers into high-n QWs (out-competing extraction, that we estimated previously to be of the order of tens of ps) where BCP can no longer extract them.…”
Section: Probing the Effect Of Organic Spacer With Two-dimensional El...mentioning
confidence: 99%
“…[17,18] This cascade proceeds via energy or charge transfer processes among the QWs in timescales up to several hundred ps. [19][20][21][22] This energy funneling approach has already been harnessed to realize highly efficient light-emitting diodes, [23,24] ultrafast charge and spin transport, [25][26][27] solar cells, [28][29][30][31][32] etc.…”
Section: Introductionmentioning
confidence: 99%
“…A recent theoretical work by Giovanni and co-workers revealed that in Ruddlesden–Popper perovskites, exciton delocalization across multiple quantum wells may be responsible for coherent Dexter-like energy transfer between layers . Furthermore, their model suggests that coherent energy funneling is most pronounced in low n phases, which have dominated experimental studies of interlayer energy transfer.…”
Section: Interlayer Sensitized Triplet Emission In 2d Metal-halide Pe...mentioning
confidence: 99%
“…Here, the authors demonstrate that excitons in PEPI are delocalized for about 10 nm in the direction perpendicular to the barriers [143]. It is noteworthy that these subbands could provide a mechanism for ultrafast and coherent energy transfer: this would be possible in mixed RPs by the excitation of a selected n-phase and the subsequent collapse of the delocalized wavefunction on higher n-phase at lower energy [144].…”
Section: Please Cite This Article As Doi: 101063/50031821mentioning
confidence: 71%